Annealing effect on synthesized ZnS/TiO2 nanocomposite for treatment of industrial wastewater. (4th October 2019) - Sattar, U; Ikram, M; Junaid, M; Aqeel, M; Imran, M; Ali, S
Abstract: Low cost and easy sol-gel process was adopted to synthesize ZnS/TiO2 nanocomposites and annealed at different temperatures 100, 450, 750 and 1050 °C. X-ray diffraction (XRD) analysis revealed that crystallinity increased gradually with increasing temperature and TiO2 phase transformed from bulk to anatase at 450 °C, anatase to rutile at 750 °C and 1050 °C respectively. It was observed from obtained UV-visible spectra that absorption increased with temperatures and reduction in bandgap energies from 3.31 to 3.0 eV. Fourier transform infrared (FTIR) spectroscopy confirmed the presence of Ti–O bonding correspond to 450–500 cm −1 and phase formation was confirmed by Raman spectroscopy. Filed emission scanning electron microscopy (FESEM) images portrayed the presence of flower flakes like particles (100 °C), nanorods (450 °C) and agglomerations of nanocomposites were seen with higher temperatures. Photocatalytic measurements of nanocomposite were considered by irradiating methylene blue (MB) dye solution under visible light. It was noted that nanocomposite at low temperature bleaches out methylene blue more than higher temperature.